Influence of food groups on plasma total homocysteine for specific MTHFR C677T genotypes in Chinese population. Issue 2 (4th October 2016) - Zeng, Qiang; Li, Fan; Xiang, Tianyuan; Wang, Weimin; Ma, Cong; Yang, Chao; Chen, Haixu; Xiang, Hang
Abstract : The influence of diet on plasma total homocysteine for specific MTHFR C677T genotypes in Chinese population is investigated. There are correlations between homocysteine (Hcy) levels and the frequency (F) and quantity (Q) of food groups for specific genders and genotypes. For male CC group, fish (F) was negatively correlated with Hcy; or female CC group, fruit/vegetable (Q), egg (F) and meat (F) were negatively correlated with Hcy, but soy (F) was positively correlated with Hcy. Abstract : Scope: It has been demonstrated that a mutation of MTHFR C677T increases plasma total homocysteine (Hcy) concentration and decreases folate. Natural foods can improve Hcy levels, but the effect of certain foods remains undetermined. The aim of this study was to investigate the association between food groups and Hcy, and to explore the correlations between Hcy and dietary folate/vitamin (Vit) B12 for genotype‐specific population. Methods and results: A total of 4507 adults were enrolled in this study, all of whom underwent physical examinations and genotyping. A dietary recall questionnaire, which assessed the frequency (F) and quantity (Q) of food consumption, was completed by all. For the male CC group, after adjustment for age and BMI, fish (F) was negatively correlated with Hcy; for the male CT group, fish (F) and eggs (F) were negatively associated with Hcy, whereas cereal/wheat (Q) were positively correlated with Hcy; for the male TT group, fish (F), meat (Q), milk (F), and fruits/vegetables (Q) were negatively associated with Hcy, whereas sugar (Q) and salt (Q) were positively associated with Hcy. For the female CC group, fruits/vegetables (Q), eggs (F) and meat (F) were negatively correlated with Hcy, but soy (F) was positively correlated with Hcy; for the female CT group, eggs (F) and meat (Q) were negatively correlated with Hcy, whereas soy (F), fried foods (F) and salt (Q) were positively correlated with Hcy; for the female TT group, fish(F), eggs (F), and fruits/vegetables (F) were negatively associated with Hcy. Furthermore, we found that Hcy was more closely correlated with folate than with Vit B12 for males (CC, CT and TT) and female TT genotype. However, the correlation between Hcy and Vit B12 was stronger for the female CT/CC groups. Conclusion: Hcy levels were influenced by food groups to varying degrees, which were based on gender and MTHFR C677T genotypes. Hcy levels were more closely correlated with folate for males (CC, CT and TT) and the female TT group, but it was more closely correlated with Vit B12 for the female CT/CC groups.